Journal for the Advancement of Developing Economies 2018
DOI: 10.13014/k2445jp5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Work Values and Individual Attributes on Citizenship and Task Performance: A Test in a Developing Country Context

Abstract: This study examined the impact of work values and individual characteristics on organizational citizenship behavior (OCB) and task performance (TP). Based on the arguments of Social Capital Theory, a theoretical foundation was developed to use work values as antecedents of OCB. Analyzing 416 responses from Sri Lankan manufacturing sector employees, it was found that gender and employment category were related to citizenship performance, while level of education was related to task performance. More importantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 65 publications
(79 reference statements)
2
2
0
Order By: Relevance
“…In confirmation with earlier studies (Azila-Gbettor et al. , 2020; Feather and Rauter, 2004; Liang, 2012; Chadrakumara et al. , 2010), support was found between AWV and customer OCB.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In confirmation with earlier studies (Azila-Gbettor et al. , 2020; Feather and Rauter, 2004; Liang, 2012; Chadrakumara et al. , 2010), support was found between AWV and customer OCB.…”
Section: Discussionsupporting
confidence: 91%
“…In confirmation with earlier studies (Azila-Gbettor et al, 2020;Feather and Rauter, 2004;Liang, 2012;Chadrakumara et al, 2010), support was found between AWV and customer OCB. The inference of this result is that employees who possess AWVs, including helping people, valuing social interaction, etc., are likely to exhibit them to support customer OCB within family hotels.…”
Section: Servant Leadership and Customer Ocbsupporting
confidence: 91%
See 2 more Smart Citations